2018
DOI: 10.1101/489419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macroevolutionary bursts and constraints generate a rainbow in a clade of tropical birds

Abstract: Media Submission 25How do elaborately coloured animals evolve? In this study we investigated the brush-tongued parrots, the lories and lorikeets, to identify the evolutionary patterns that gave rise to spectacular ornamentation in nature. We found that these parrots are as colourful as all other birds combined, and that multiple evolutionary trends combine to generate their remarkable colour palette. Feather regions that would make birds more visible to predators had constrained evolution, 30 whereas those lik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Darker parrots are more frequent in wetter environments, as predicted by Gloger's rule (Rensch, 1936). Support for Gloger's rule has already been found at the intraspecific level in parrots (in the crimson rosella Platycercus elegans ; Ribot et al., 2019) and also at the interspecific level among lorikeets (Merwin et al., 2020). We now show that it is a general pattern that applies at the interspecific level based on all 398 extant parrot species.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Darker parrots are more frequent in wetter environments, as predicted by Gloger's rule (Rensch, 1936). Support for Gloger's rule has already been found at the intraspecific level in parrots (in the crimson rosella Platycercus elegans ; Ribot et al., 2019) and also at the interspecific level among lorikeets (Merwin et al., 2020). We now show that it is a general pattern that applies at the interspecific level based on all 398 extant parrot species.…”
Section: Discussionmentioning
confidence: 84%
“…Different studies have evaluated how abiotic factors affect bird plumage colour evolution and a variety of hypotheses have been proposed to explain colour variation both within and across avian taxa (Dale et al., 2015; Merwin, Seeholzer, & Smith, 2020; Miller et al., 2019; Ribot, Berg, Schubert, Endler, & Bennett, 2019). Previous studies showed that achromatic (light‐to‐dark) variation in birds is related to climate variables such as temperature and precipitation (Delhey, 2017, 2018, 2019; Heidrich et al., 2018; Merwin et al, 2020; Miller et al., 2019; Pinkert, Brandl, & Zeuss, 2017; Ribot et al., 2019). Specifically, a negative relationship between melanin pigmentation and temperature has been reported in several taxa (Delhey, 2018; Heidrich et al., 2018; Pinkert et al., 2017), in support of the thermal melanism hypothesis (Clusella Trullas, van Wyk, & Spotila, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dichromatism has the advantage of being easier and more objective to compute compared to cross‐species scores of colour elaboration, because conspecific males and females usually differ only in the degree to which they express an identical pattern of ornamentation, and different species often differ on multiple aspects of ornamentation that are difficult to integrate and compare in a biologically‐relevant manner. This is an important advantage because, for example, plumage coloration in different body parts of parrots may have different functions and patterns of evolution (Merwin et al, 2020). Moreover, different colours or body parts may also differ in the degrees to which they evolve sexual dichromatism (Taysom et al, 2011), all of which complicate the comparison of ornamentation, especially between species differing strongly in their pattern of plumage colour ornamentation.…”
Section: Discussionmentioning
confidence: 99%
“…2018, 2020; Merwin et al. 2020; Wylde and Bonduriansky 2020; Avendaño and Cadena 2021). Additionally, there is an equally robust body of literature characterizing phenotypic variation to understand how selection shapes individual diversity within a given species (Westcott 1992; Loyau et al.…”
Section: Discussionmentioning
confidence: 99%
“…2014; Merwin et al. 2020). However, addressing this objective can be incredibly challenging, especially when display behavior is highly complex (Melo and Marroig 2015; Wilkins et al.…”
mentioning
confidence: 99%